Analisis Perbedaan Anggaran, Realisasi dan Daya Serap Belanja Daerah (Provinsi Sumatera Utara dan Provinsi Jawa Tengah) - Juliati Juliati; Trisninik Ratih Wulandari; Arum Kusumaningdyah Adiati (Jurnal Akuntansi dan Pajak, 2022)
This study is to determine whether there are differences in the budget, realization and absorption of regional expenditures in districts in North Sumatra and Central Java provinces. The data used in this study are 31 regencies in North Sumatra Province and 29 regencies/cities in Central Java Province. This study uses the Mann Whitney Non-Parametric Test to test whether there are differences in budget, realization and absorption in districts/cities in the two provinces. The results of this study indicate that the first hypothesis is accepted, the second hypothesis is accepted for operational expenditure realization, capital expenditure realization and regional expenditure realization, while the third hypothesis is rejected.